Depressão e insuficiência renal crônica: representações sociais de pacientes em hemodiálise e cuidadores. - Costa, Fabrycianne Gonçalves (2013)
This study aimed to apprehend the social representations about depression and Chronic Renal Failure (CRF) elaborated by nephrological patients in dialysis treatment and their caregivers, with and without depressive symptoms. Specifically, we sought to measure the rate of depression in nephrological patients and their caregivers; relate bio-sociodemographic variables of patients and their caregivers with the depression; analyze the different representational semantic fields about CRF, treatment, hemodialysis, and depression and, finally, verify the consensus and dissent of social representations elaborated by participants in the context of CRF. It was treated as a field research, descriptive, qualitative and quantitative, having as theoretical basis the Social Representations. The locus of the research comprehended three hospitals that provide treatment of hemodialysis for adults and maintain agreement with the SUS. The sample type was non-probabilistic and by convenience, comprised 50 patients with ages between 20 and 73 years (M= 46.05; SD =13.4)and 50 caregivers aged 18 to 68 years (M= 40,7; SD=14.0). Were used as instruments: a bio-sociodemographic questionnaire,the hospital scale for anxiety and depression HADS-D (specifically the sub-depression scale), the technique of free association of words and a semi-structured interview. For processing of data were performed descriptive and inferential statistics (chi-square,Pearson and Spearman's correlation). The evocations were analyzed by correspondence factorial analysis, and interviews were processed by Alceste (descending and ascending hierarchical analysis and cross-table analysis). The results indicated that 20% of patients and 46% of caregivers have symptoms of depression. There was a positive correlation (r= (0.37); p=0.008) between time of monitoring of caregivers and depression, suggesting that the as longer the duration of care, the higher is the level of depression of these accompanying. The CRF was represented by caregivers as synonymous of difficult disease. Renal patients have associated the disease complexity with their treatment(difficult), being objectified as an incurable disease and of unknown cause. Depression was objectified as bad. Participants have anchored the know in the physical-organic and psychoaffective aspects, highlighting their historical and factual experiences at the difficulty in treating the disease, namely hemodialysis and its multiple meanings (death and life). The analysis revealed five classes of the Alceste, "Meanings of depression", "Family support in the context of CRF", "Support spiritual in the treatment", "Nutritional factors", and "Discovering the diagnosis". Cross-analysis revealed that patients' representations are linked to treatment and of the caregivers is related to support to family members. Although patients show a high rate of depression, the prevalence of the disease in caregivers was spare. This fact points to the need to confront the problem not only in the context of the nephrological group, but also in the context of the caregivers who, in general, experience, joint with patients, the limitations imposed by the disease.